Feshbach-like study of He resonant states in Debye plasmas using explicitly correlated wave functions (2012)
ABSTRACT: We present a study on the 1;3Se, 1;3Po and 1;3De He resonant states below the He+ (N=2) threshold under the in uence of a plasma environment, when the Debye screening length is varied. The interaction between all charged particles is modeled with Yukawa-like screened Coulomb potentials. We make use of the Feshbach projector method to characterize resonant states, implemented by using explicitly correlated CI-wave functions.